¿Es frecuente la depresión mayor en la psoriasis? - Veintimilla, Paola (2017)
Context: psoriasis is a dermatological pathology with important psychological consequences derived from the stigma generated by the striking appearance of the lesions, especially, isolation, anxiety, major depression and increase in suicidal ideas.Objective: to determine the degree of depression in patients with the degree of severity of psoriasis.Subjects and methods: a descriptive, cross-sectional study was conducted with random sampling in 82 patients with psoriasis, of both sexes, without previous diagnosis of depression, aged between 15 and 90 years, who attended the outpatient service of the Hospital’s Dermatology service. Carlos Andrade Marín, in the period July-August 2015. By means of the Beck test, the degree of depression and PASI index (Psoriasis Area Severity Index) was determined, the degree of psoriasis was estimated.Results: the prevalence of depression was 24.4%; Statistical association was found between depression and severity of psoriasis. The female sex showed 3.5 times more risk to present depression with respect to the male sex; Subjects with severe psoriasis have a 35.7 times higher risk of depression compared with patients suffering from mild psoriasis.Conclusion: the prevalence of depression is high and increases with the degree of severity of psoriasis, it is suggested to include in the routine management the psychological and psychiatric follow-up; it is recommended to implement prospective studies to determine the evolution of psychiatric comorbiditiesin this population group, in order to design treatment protocols adjusted to the Ecuadorian population